2006
DOI: 10.1001/archotol.132.10.1035
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Survival Rates for Young Blacks With Nasopharyngeal Carcinoma in the United States

Abstract: To compare the incidence rates of nasopharyngeal carcinoma (NPC) among US black, white, and Asian/Pacific Islander (Asian) populations, with a focus on those diagnosed before age 20 years and between ages 20 and 29 years. Our secondary objective was to determine differences in survival rates between US blacks, whites, and Asians with NPC who were younger than 30 years. Design: Data from the National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) tumor registry system were used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
3
30
1
Order By: Relevance
“…114 "Asians" had a higher incidence of NPC and better survival for all types and stages compared to the other groups. This is at variance with the study by Richey et al 115 who reported limited variation in the 2-and 5-year survival rates between different ethnic groups. Based on SEER data, Bhatacharyya found, that the overall survival was better among Chinese patients (in the US) compared to whites, but the disease-specific survival was similar between the 2 groups.…”
Section: Staging Treatment Prognosis and Risk Of Secondary Malignacontrasting
confidence: 90%
See 1 more Smart Citation
“…114 "Asians" had a higher incidence of NPC and better survival for all types and stages compared to the other groups. This is at variance with the study by Richey et al 115 who reported limited variation in the 2-and 5-year survival rates between different ethnic groups. Based on SEER data, Bhatacharyya found, that the overall survival was better among Chinese patients (in the US) compared to whites, but the disease-specific survival was similar between the 2 groups.…”
Section: Staging Treatment Prognosis and Risk Of Secondary Malignacontrasting
confidence: 90%
“…Interestingly, in their study (based on SEER data), Richey et al found that in patients o30 years, blacks had the highest incidence rate of NPC. 115 It should be noted, however, that although the SEER database is the largest cancer registry in the US, studies comparing different ethnic groups based on the SEER data, have limitations. One obvious limitation is the fact that the ethnic and geographical origin is not particularly detailed.…”
Section: Staging Treatment Prognosis and Risk Of Secondary Malignamentioning
confidence: 99%
“…Over the last three decades, the incidence rates of nasopharyngeal carcinoma decreased significantly in southern and eastern Asian [19], while the incidence rate in the United States have remained almost unchanged [20]. The survival rates for each AJCC stage and histological subtype have exhibited considerable improvement over time, especially in Asians due to more favorable undifferentiated histology in this group [21].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 These findings coincide with those of the National Cancer Institute (USA), showing a higher incidence of nasopharyngeal carcinomas in young adult Caucasians and Afro-Americans compared to Asian patients. 14 Tobacco and alcohol are relevant etiological factors in upper digestive airways. Undifferentiated nasopharyngeal malignancies, however, are less affected by these substances, which are not considered etiological in these cases.…”
Section: Discussionmentioning
confidence: 99%